Advanced Climate Data Tool (CDT) Training and Automatic Weather Station Data Tool (ADT) Part II for Kenya Meteorological Department (KMD) - Dinh, Dannie (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
In October 2022, the International Research Institute for Climate and Society (IRI) conducted an advanced training on Climate Data Tool (CDT) and Automatic Weather Station Data Tool (ADT) for Kenya Meteorological Department (KMD) staﬀ in Nairobi, Kenya. The training involved software installation and hands-on instructional sessions at the KMD head oﬃce. The installation and training was requested by the KMD to support and improve the access and processing—including quality control and visualization—of automatic weather station (AWS) data collected by diﬀerent systems and networks, on diﬀerent servers, and in diﬀerent formats.